Autophagy induced by infectious pancreatic necrosis virus promotes its multiplication in the Chinook salmon embryo cell line CHSE-214. Issue 97 (February 2020) - Dong, Ying; Zhao, Jingzhuang; Chen, Xiaoyu; Liu, Miao; Ren, Guangming; Lu, Tongyan; Shao, Yizhi; Xu, Liming
Abstract: Infectious pancreatic necrosis virus (IPNV) is a common pathogen that causes huge economic losses for the salmonid aquaculture industry. Autophagy plays an important regulatory role in the invasion of pathogenic microorganisms. In this study, we explored the relationship between IPNV infection and autophagy in Chinook salmon embryo (CHSE-214) cells using standard methods. Transmission electron microscopy showed that IPNV infection produced typical structures of autophagosomes in CHSE-214 cells. Transformation of microtubule-associated protein 1 light chain 3 (LC3)-I to LC3-II protein, a marker of autophagy, was observed in IPNV-infected cells using confocal fluorescence microscopy and western blot analysis. Western blotting also showed that expression of the autophagy substrate p62 was significantly decreased in IPNV-infected cells. The influence of autophagy on IPNV multiplication was further clarified with cell culture experiments using autophagy inducer rapamycin and autophagy inhibitor 3-methyladenine. Rapamycin promoted IPNV multiplication at both the nucleic acid and protein levels, which led to higher IPNV yields; 3-methyladenine treatment had the opposite effect. This study has demonstrated that IPNV can induce autophagy, and that autophagy promotes the multiplication of IPNV in CHSE-214 cells. Highlights: This study firstly reveals that IPNV could induce autophagy in CHSE-214 cell line. The autophagy promotes IPNV replication and benefits IPNV yield. Autophagy plays an important role for IPNV infection in CHSE-214 cell line.